2021
DOI: 10.1016/j.ekir.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Use and Safety of Remdesivir in Kidney Transplant Recipients With COVID-19

Abstract: Introduction Remdesivir has demonstrated antiviral activity against coronavirus, shortening the time to recovery in adults hospitalized with moderate/severe COVID-19. Severe adverse events such as acute kidney injury (AKI) have been reported. There is little available data on the use and safety of remdesivir in kidney transplant (KT) recipients. Methods We present a multicenter cohort study of 51 KT recipients with COVID-19 treated with remdesivir. Outcomes and safety w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…The other recipients recovered, and no major adverse events were noted for remdesivir, including liver dysfunction [78]. A multicenter cohort study of 51 KTRs with COVID-19 who were treated with remdesivir found a mortality rate of 18.9%, with no significant hepatoxicity or systemic symptoms that resulted from the drug [79]. Forty-two KTRs with COVID-19 (19% with moderate disease and 43% with severe disease) received antiretrovirals (n = 10) or remdesivir (n = 8) as part of COVID-19 management.…”
Section: Antiviral Therapy In Covid-19mentioning
confidence: 98%
“…The other recipients recovered, and no major adverse events were noted for remdesivir, including liver dysfunction [78]. A multicenter cohort study of 51 KTRs with COVID-19 who were treated with remdesivir found a mortality rate of 18.9%, with no significant hepatoxicity or systemic symptoms that resulted from the drug [79]. Forty-two KTRs with COVID-19 (19% with moderate disease and 43% with severe disease) received antiretrovirals (n = 10) or remdesivir (n = 8) as part of COVID-19 management.…”
Section: Antiviral Therapy In Covid-19mentioning
confidence: 98%
“…11 were no significant safety concerns with drug administration. 17 The study included 48 subjects taking RDV known to have comorbid diseases (cardiovascular disease, asthma, pulmonary disease, cancer, liver disease, kidney disease, diabetes and HIV). In this study 102 adverse drug reactions (ADRs) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…16 T-cell mediated rejection and thrombotic microangiopathy were also known to occur with RDV. 17 Hepatobiliary disorders, acute renal failure, and nervous system disorders had also been reported in the studies we reviewed. Overall, the side effects that occurred in patients taking RDV were not significantly different from the control group,…”
Section: Safety Of Remdesivirmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been shown that 74% of remdesivir and its active metabolite are eliminated by the kidneys, and 18% are eliminated through feces. Remdesivir is not recommended in patients with severe renal insufficiency, but some studies have shown that the usual dose of remdesivir might be safe for patients with severe renal insufficiency [ 36 ], end-stage renal disease on hemodialysis [ 37 ], or kidney transplantation [ 38 ].…”
Section: Remdesivirmentioning
confidence: 99%